A novel inhaled phosphodiesterase 4 inhibitor (CHF6001) reduces the allergen challenge response in asthmatic patients. (October 2016) - Singh, D.; Leaker, B.; Boyce, M.; Nandeuil, M.A.; Collarini, S.; Mariotti, F.; Santoro, D.; Barnes, P.J.
Abstract: CHF6001 is an inhaled phosphodiesterase 4 (PDE4) inhibitor in development for the treatment of obstructive lung diseases. The efficacy and safety of CHF6001 were investigated in a double blind, placebo controlled, 3-way cross-over study using the allergen challenge model. Thirty-six atopic asthmatics who were not taking inhaled corticosteroids and who demonstrated a late asthmatic response (LAR) to inhaled allergen at screening were randomised to receive CHF6001 400 μg or 1200 μg or placebo administered once a day using a dry powder inhaler. The three treatment periods were 9 days; allergen challenges were performed on day 9 and induced sputum was obtained after 10 h from challenge. Washout periods between treatments were up to 5 weeks. Both CHF6001 doses significantly attenuated the LAR; the primary endpoint analysis showed that CHF6001 400 μg and 1200 μg caused reductions of 19.7% (p = 0.015) and 28.2% (p < 0.001) respectively of the weighted FEV1 AUC4–10h compared with placebo. The difference between the CHF6001 doses was not statistically significant (p = 0.223). Compared with placebo, CHF6001 caused greater reduction in sputum eosinophil counts, although these changes were not statistically significant. CHF6001 was well tolerated, with similar numbers of adverse events in each treatment period. This inhaled PDE4 inhibitor has the potential to provide clinical benefits in patients with atopic asthma.